Influence of ethrel and calcium carbide on respiration rate, ethylene evolution, electrolyte leakage and firmness of'Dashehari' mango (Mangifera indica) - PAL, R K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted on the effect of treatment on mature unripe 'Dashehari' mangoes (Mangifera indica L.)with 200 or 400 ppm a i of ethrel and subsequent storage in evaporative-cool-chamber (25-28Â°C and 85-90% relativehumidity) resulted in better ripening attributes. High dose of ethrel (600 ppm) or calcium carbide treatment gave moreelectrolyte leakage from the pulp resulting poor textural properties during ripening. Low dose of ethrel maintainedbetter fruit firmness on ripening compared with the calcium carbide treated fruits irrespective of the storage environment.A rational dose of 200 or 400 ppm active ingredient of ethrel application was found to be ideal for ripening of 'Dashehari'mangoes.